2020
DOI: 10.3390/app10020456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Owinema Bio-Preparation on Vermicomposting in Earthworm Ecological Boxes

Abstract: This paper describes vermicomposting of kitchen organic waste with the use of Eisenia fetida earthworms in an ecological box. To control excessively proliferated Sciaridae in the box medium, an Owinema bio-preparation, which contains larvae of the nematode Steinernema feltiae, was used. The effect of this bioinsecticide on the earthworm population during vermicomposting of organic waste was assessed. It was found that the applied bio-preparation effectively limited the population of sciarids and also had a pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Sims and Gerard [ 18 ] recognized 3000 species, Sinha et al [ 19 ] reported 4400, while Grdiša et al [ 20 ] reported that 7000 species had been recorded. Approximately 40 of these species have been described in Poland, of which some, e.g., D. veneta or E. fetida , can be easily bred as they are used in the vermicomposting process of selected organic waste [ 21 , 22 , 23 ]. This process allows the transformation of segregated organic waste into biofertilizer-vermicompost, which can form a part of the circular economy [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sims and Gerard [ 18 ] recognized 3000 species, Sinha et al [ 19 ] reported 4400, while Grdiša et al [ 20 ] reported that 7000 species had been recorded. Approximately 40 of these species have been described in Poland, of which some, e.g., D. veneta or E. fetida , can be easily bred as they are used in the vermicomposting process of selected organic waste [ 21 , 22 , 23 ]. This process allows the transformation of segregated organic waste into biofertilizer-vermicompost, which can form a part of the circular economy [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The collection of earthworms began in September-November 2020 from the home garden, as the samples were collected by digging the soil 15-30 cm deep for the soil and more. They were preserved and bred in plastic boxes with dimensions (20×27×38 cm) These boxes contained a piece of cloth that was placed at the bottom of the box and extended to its sides, and soil and bird droppings were placed in these boxes according to the method (9,10). Also, dilute concentrations of this pesticide were prepared.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Since earthworms are non-target soil invertebrates that are affected by the use of pesticides because it has direct contact with the soil and thus its tissues are rapidly exposed to chemicals and accumulate in their tissues (25). Thus, earthworms response to applying pesticides to soil can provide information about their tolerance limits and their ability to treat the toxic effects of pesticides pests (10).…”
Section: Introductionmentioning
confidence: 99%